Computational flow cytometry reveals that cryopreservation induces spermptosis but subpopulations of spermatozoa may experience capacitation-like changes. Issue 3 (March 2017) - Ortega-Ferrusola, C; Anel-López, L; Martín-Muñoz, P; Ortíz-Rodríguez, J M; Gil, M C; Alvarez, M; de Paz, P; Ezquerra, L J; Masot, A J; Redondo, E; Anel, L; Peña, F J
Abstract : The reduced lifespan of cryopreserved spermatozoa in the mare reproductive tract has been attributed to both capacitative and apoptotic changes. However, there is a lack of studies investigating both phenomena simultaneously. In order to improve our knowledge in this particular point, we studied in raw and frozen-thawed samples apoptotic and capacitative markers using a wide battery of test based in flow cytometry. Apoptotic markers evaluated were caspase 3 activity, externalization of phosphatidylserine (PS), and mitochondrial membrane potential. Markers of changes resembling capacitation were membrane fluidity, tyrosine phosphorylation, and intracellular sodium. Conventional and computational flow cytometry using nonlinear dimensionally reduction techniques ( t -distributed stochastic neighbor embedding (t-SNE)) and automatic classification of cellular expression by nonlinear stochastic embedding (ACCENSE) were used. Most of the changes induced by cryopreservation were apoptotic, with increase in caspase 3 activation ( P  < 0.01), PS translocation to the outer membrane ( P  < 0.001), loss of mitochondrial membrane potential ( P  < 0.05), and increase in intracellular Na+ ( P  < 0.01). Average values of markers of capacitative changes were not affected by cryopreservation; however, the analysis of the phenotype of individual spermatozoa using computational flow cytometry revealed the presence of subpopulations of spermatozoa experiencing capacitative changes. For the first time advanced computational techniques were applied to the analysis of spermatozoa, and these techniques were able to disclose relevant information of the ejaculate that remained hidden using conventional flow cytometry.